Body Mass Index and Hospital Mortality in Patients with Acute Coronary Syndrome Receiving Care in a University Hospital - Mercedes Camprubi; Sandra Cabrera; Jordi Sans; Georgina Vidal; Teresa Salvadó; Alfredo Bardají (Journal of Obesity)
Although obesity is a well-established cardiovascular risk factor, some controversy has arisen with regard to its effect on hospital mortality in patients admitted for acute coronary syndrome. Methods. Clinical and anthropometric variables were analyzed in patients consecutively admitted for acute coronary syndrome to a university hospital between 2009 and 2010, and the correlation of those variables with hospital mortality was examined. Results. A total of 824 patients with a diagnosis of myocardial infarction or unstable angina were analyzed. Body mass index was an independent factor in hospital mortality (odds ratio 0.739 (IC 95%: 0.597-0.916), P=0.006). Mortality in normal weight (n=218), overweight (n=399), and obese (n=172) subjects was 6.1%, 3.1%, and 4.1%, respectively, with no statistically significant differences between the groups. Conclusions. There is something of a paradox in the relationship between body mass index and hospital mortality in patients with acute coronary syndrome in that the mortality rate decreases as body mass index increases. However, no statistically significant differences have been found in normal weight, overweight, or obese subjects.